A Preliminary Test of the Association between Agnew's Social Concern and Criminal Behavior: Results from a Nationally Representative Sample of Adults. Issue 2 (1st February 2019) - TenEyck, Michael; Barnes, J.C.
ABSTRACT: In his Presidential Address to the American Society of Criminology, Agnew proposed a new theory of crime causation referring to the key independent variable as "social concern." Social concern theory highlights the nuanced association between self-interest, altruistic behavior, and criminal behavior. Although there is considerable indirect evidence to support the theory—indeed, it is an example of inductive theory construction—there have been few direct tests of Agnew's statements. As a result, the current study represents one of the first tests of social concern theory by examining the direct relationship between social concern and criminal behavior. We also test whether social concern mediates the effect of sex on criminal behavior, thereby offering insight into the gender gap in offending. Drawing on data from a nationally representative sample of American adults, we perform exploratory factor analysis to construct a measure of social concern. Results from negative binominal regression models reveal that social concern is negatively associated with criminal behavior even after controlling for a host of potential confounders. Additionally, findings indicate a portion of the gender gap in criminal offending may be attributable to females' (generally) higher levels of social concern.